Trauma and Unconcius Desire of Main Character in Dracula: A Love Tale Movie Psychoanalytic Approach - Putri Kerli Triana; Tatu Novyawati Zahwa; Euis Meinawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explores how trauma shapes the unconscious motivations of the main character in Dracula: A Love Tale by applying Freud’s psychoanalytic framework. The researchers aim to identify how the character’s emotional breakdown and long-term grief affect the relationship between the id, ego, and superego. Using a descriptive qualitative method, nine key dialogues were analyzed to reveal psychological patterns related to loss, denial, longing, and internal conflict. The findings show that the trauma of losing his wife consistently activates intense unconscious impulses, allowing the id to dominate through desire, obsession, and emotional volatility. Meanwhile, the ego struggles to negotiate between these impulses and reality, and the superego gradually weakens as moral and spiritual certainty collapses. The results demonstrate that unresolved trauma not only drives the character’s unconscious desires but also reshapes his behavioral patterns and overall personality development throughout the narrative.